The oral disposition index calculated from a meal tolerance test is a crucial indicator for evaluating differential normalization of postprandial glucose and triglyceride excursions in morbidly obese patients after laparoscopic sleeve gastrectomy - Yukako Yamamoto; Takeshi Togawa; Osamu Sekine; Yuki Ozamoto; Junko Fuse; Choka Azuma; Jun Ito-Kobayashi; Yasumitsu Oe; Akeo Hagiwara; Masaki Kobayashi; Tadahiro Kitamura; Masanori Iwanishi; et al. (Endocrine Journal)
To determine the normalization of postprandial blood glucose (PG) and triglyceride (TG) excursions in 30 morbidly obese patients with or without diabetes mellitus (DM) 1-year after they underwent a laparoscopic sleeve gastrectomy (LSG) vs. their pre-surgery data, we administered the 75-g oral glucose tolerance test (OGTT) and a meal tolerance test (MTT) using a 75-g glucose-equivalent carbohydrate- and fat-containing meal. The results were as follows; (i) Postoperative body-weight reduction was associated with DM remission and reduced multiple cardiometabolic risks. (ii) OGTT data showing postprandial hyper-insulinemic hypoglycemia in many post-surgery patients were associated with overdiagnosis of improved glucose tolerance. However, postoperative MTT data without hypoglycemia showed no improvement in the glucose tolerance vs. pre-surgery data. (iii) The disposition index (DI) i.e., [Matsuda index] × (Glucose-induced insulin secretion) was progressively worsened from normal glucose tolerance to DM patients after LSG. These post-surgery DI values measured by the MTT were correlated with 2h-plasma glucose levels and were not normalized in DM patients. (iv) The baseline, 2h-TG, and an increase in 2h-TG values above baseline were correlated with the insulin resistance index, DI, or HbA1c; These TG values were normalized post-LSG. In conclusion, the glucose tolerance curve measured by the MTT was not normalized in T2DM patients, which was associated with impaired normalization of the DI values in those patients 1-year after the LSG. However, the baseline TG and a fat-induced 2h-TG values were normalized postoperatively. The MTT can be used to assess normalization in postprandial glucose and TG excursions after LSG.